Design and fabricate of miniaturized T-shape ultra wideband antenna for wireless application - Al-tabatabaie, Kusay F.; Saeed, Matai N. (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
Ultra-wideband antenna (UWB) technology is based on a unique factor that symbolizes a clearer wireless broadband solution than other technologies, and its lower integration cost compared to long distances is very attractive to researchers. The UWB technology will be the key solution for the future WPAN systems. This is due to its ability to achieve very high data rate which results from the large frequency spectrum occupied. Besides, extremely low power emission level will prevent UWB systems from causing severe interference with other wireless systems. UWB design and fabrication have become very vital research area recently. This paper presents a novel T-Slot Shape Miniaturized UWB Antenna, which is capable of rejecting the interfered signal from Wireless Local Area Network (WLAN) and Fixed Wireless Access Transmitters (FWA). While, Voltage Standing wave Ratio (VSWR) is below 2, the antenna has a size of 1.5 cm length and 1.2cm width with bandwidth ranging from 3.1 to 10.6GHz. However, the ground gap and T-slot have improved the notching bandwidth, the slot type and feeding strip had been configured to have correspondingly a compact antenna patch size. The design simulated using Zeland Fidelity software and the measurements validate the simulation results to have an omnidirectional radiation pattern.